Outcomes and risk factors for functional prognosis at 3 months after intravenous thrombolysis with r-tPA in patients with acute ischemic stroke: a retrospective cohort study - Yayun Xu; Haixing Feng; Zhengzheng Huang; Yanlei Li; Feng Chi; Lijie Ren (Thrombosis Journal)
Abstract Intravenous thrombolysis (IVT) with recombinant tissue plasminogen activator (rt-PA) is the preferred treatment for acute ischemic stroke (AIS). Nevertheless, only approximately half of patients undergoing IVT experience positive outcomes. The objective of the study was to examine the clinical characteristics of patients with AIS and identify predictors for unfavorable clinical outcomes at 3 months after IVT. This retrospective cohort study comprised 3805 consecutive patients diagnosed with AIS who received IVT. Patients categorized as having a poor outcome were those with a modified Rankin scale score (mRS) of 3–6, while those categorized as having a good outcome had a score of 0–2. Clinical profiles and laboratory examinations were compared among patients with differing outcomes. A logistic regression model was utilized to investigate potential factors correlated with unfavorable outcomes. Of the 3805 patients included in the study, 3176 (83.5%) were found to have a good outcome, while 629 (16.5%) experienced an poor outcome following IVT. Advancing age (OR = 1.037, P < 0.001) and higher baseline National Institutes of Health Stroke Scale (NIHSS) scores (OR = 1.156, P < 0.001) were significant independent predictors of a poor outcome. The area under curve (AUC) values for age, NIHSS score, and the combined effect of age and NIHSS score in predicting a poor response were 0.644, 0.761, and 0.777, respectively. Our research indicates that advancing age and higher baseline NIHSS score may serve as prognostic indicators for predicting early unfavorable outcomes following IVT in patients with AIS.